Matrix type and landscape attributes modulate avian taxonomic and functional spillover across habitat boundaries in the Brazilian Atlantic Forest. Issue 11 (12th July 2019) - Barros, Fabio M.; Martello, Felipe; Peres, Carlos A.; Pizo, Marco A.; Ribeiro, Milton C.
Abstract : Land use intensification drives biodiversity loss worldwide. In heterogeneous landscape mosaics, both overall forest area and anthropogenic matrix structure induce changes in biological communities in primary habitat remnants. However, community changes via cross‐habitat spillover processes along forest–matrix interfaces remain poorly understood. Moreover, information on how landscape attributes affect spillover processes across habitat boundaries are embryonic. Here, we quantify avian α‐ and β‐diversity (as proxies of spillover rates) across two dominant types of forest–matrix interfaces (forest–pasture and forest–eucalyptus plantation) within the Atlantic Forest biodiversity hotspot in southeast Brazil. We also assess the effects of anthropogenic matrix type and landscape attributes (forest cover, edge density and land‐use diversity) on bird taxonomic and functional β‐diversity across forest–matrix boundaries. Alpha taxonomic richness was higher in forest edges than within both matrix types, but between matrix types, it was higher in pastures than in eucalyptus plantations. Although significantly higher in forests edges than in the adjacent eucalyptus, bird functional richness did not differ between forest edges and adjacent pastures. Community changes (β‐diversity) related to species and functional replacements (turnover component) were higher across forest–pasture boundaries, whereas changes related to species and functional loss (nested component) were higher across forest–eucalyptus boundaries. Forest edges adjacent to eucalyptus had significant higher species and functional replacements than forest edges adjacent to pastures. Forest cover negatively influenced functional β‐diversity across both forest–pasture and forest–eucalyptus interfaces. We show the importance of matrix type and the structure of surrounding landscapes (mainly forest cover) on rates of bird assemblage spillover across forest‐matrix boundaries, which has profound implications to biological fluxes, ecosystem functioning and land‐use management in human‐modified landscapes. Abstract :